Pengaruh Motivasi Kerja ,Lingkungan Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Agro Perak Sajahtera Bengkulu Utara - Armada, Armada; Bahrun, Khairul (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Employees are a very valuable asset in achieving company goals. As an employee, when carrying out work you must be as effective and efficient as possible. The quality and quantity of employees must be in accordance with employee needs and the placement of workers must also be appropriate and in accordance with their desires and skills. In this way, employee performance will be better and more effective in supporting the realization of company goals. This thesis is to analyze the influence of work motivation, work environment and job satisfaction on employee performance at PT. Agro Perak Sajahtera, North Bengkulu, sampling in this research was total sampling. are 55 employees of PT. Agro Perak Sajahtera, North Bengkulu. Multiple linear regression analysis with hypothesis testing, with the research results it can be concluded that all independent variables, namely variables (Work Motivation, Work Environment and Job Satisfaction) simultaneously or together have a significant effect on the dependent variable, namely Employee Performance (Y). This means Ho is rejected and Ha is accepted. It can be concluded that work motivation, work environment and job satisfaction together have a significant effect on employee performance at PT. Agro Perak Sajahtera, North Bengkulu.